Políticas públicas voltadas ao desenvolvimento rural sustentável: a eficácia da execução orçamentária - Ferreira, Welinton Camargo (2016)
With the construction of the Itaipu Hydroelectric Power Plant dam, the West Region of Paraná underwent a major social, political, economic and environmental restructuring. One of the greatest challenges imposed on the region was to develop its agrarian potential in a sustainable manner, in view of the impact that Itaipu has caused. The study investigated the structures aimed at the sustainable rural development of the region in the 12 municipalities bordering the lake of Itaipu on the Brazilian side. Interviews were carried out with the managers of the Secretariats of Agriculture and Environment and the data on the production of family agriculture were collected; The main environmental problems faced and the needs of these managers for the development of their actions. The results, treated in percentage, showed that contamination of water and soil and lack of financial resources were the priority environmental problems, followed by the hiring of personnel and the acquisition of equipment as the needs of these departments for the development of their actions. In the next stage a study was carried out in the period from 2010 to 2013, which analyzed the effectiveness of public policies aimed at sustainable rural development in the management of this budget. Data were collected from secondary sources with statistical treatment by means of indices. Efficacy was first measured in the State of Paraná. The Federal Government, the State of Paraná and the Municipalities of Lindeiros were compared with the State of Paraná. The results indicated that the managers of the Lindeiros Municipalities were more effective in managing their budgets relative to functions for rural development than the Federal Government and the State of Paraná together.